Program Di9ital Prayer Time Dalam Penentuan Waktu Salat - Fitri Yani; Syaifur Rizal Fahmy (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2019)
Indonesia still has problems about the time of shalat. This reason that encourage Hendro Setyanto to create a new tool in the form of a display of prayer times of all time with a new concept, Di9ital Prayer Time. This digital clock has been published and has been traded to the public. Thus, this study will examine the method and accuracy of the Di9ital Prayer Time in determining the time of prayer. Regarding this theme, this research is a type of qualitative research using an empirical juridical approach. The specification of this study is descriptive analysis, this study intends to provide an overview, examine, explain then analyze the level of accuracy of the Di9ital Prayer Time in determining the time of prayer. The results of this study indicate that after comparing the Di9ital Prayer Time with the schedule of time for the circular prayer of the Ministry of Religion, only a maximum difference of three minutes was found. If the Di9ital Prayer Time is compared to the results of the program of prayer time by Rinto Anugraha, only a difference of four minutes was found, but after being traced, the program for the Rinto prayer did not yet use ikhtiyat. If the results of the Rinto prayer time program are supplemented by two minutes of faith, the difference is a maximum of two minutes. As such, Di9ital Prayer Time is very relevant as a guideline for prayer times. While the determination of the time of prayer by the Indonesian Ministry of Religion which has been the guideline of the people throughout Indonesia is still relevant as a guideline for prayer times. This is still within the limits of relevance, given the schedule of prayer times by the Ministry of Religion is very helpful for the community.